ANALISIS KONTRIBUSI PENERIMAAN PAJAK RESTORAN TERHADAP PENDAPATAN ASLI DAERAH (PAD) PADA BADAN PENGELOLAAN KEUANGAN,PENDAPATAN DAN ASET DAERAH KOTA SIBOLGA - Dini Gusti Aldila; Nur Ainun Hasibuan; Sriayu Aritha Panggabean3 (KOLONI, 2023)
This study aims to determine the contribution of restaurant taxes to local revenue (PAD) in Sibolga City in 2017-2021. This type of research is quantitative descriptive research. The data used is data on the Budget Realization Report of the Financial Management Agency, Revenue and Regional Assets of the City of Sibolga for 2017-2021. The technique used in this study uses the contribution analysis method. The results of the study show that restaurant tax in the 2017-2021 period has reached the target of restaurant tax revenue with an average target of 139.49%. The highest restaurant tax revenue was achieved in 2018 of 173.33%, and the lowest in 2020 of 95.27%. Restaurant tax has a contribution to local revenue (PAD). The average Restaurant Tax contribution given in the 2017-2021 period is 1.91%. The biggest contribution occurred in 2019, namely 2.85%. The smallest contribution occurred in 2017, namely 0.83%. From the results of this study, it can be concluded that the Contribution of Restaurant Taxes is very lacking in Sibolga City's Local Revenue (PAD) for 2017-2021. Keywords: Restaurant Tax, Regional Original Income (PAD)